Jejak angka nol : perjalanan angka dari india, melintasi dunia islam, sampai ke eropa - ummah, revalia syafiul (Maliki Interdisciplinary Journal, 2026)
This study traces the historical development of the concept of numbers, particularly the number zero, from its origins in Indian civilization to its widespread use in Europe through the transmission of knowledge within the Islamic world. The concept of zero was first systematically formulated in India in the early centuries CE, when mathematicians such as Brahmagupta introduced a special symbol to denote “nothingness” and established its operational rules (Plofker, 2007; Ahmed, 2020). This innovation not only simplified numerical notation systems but also opened space for the development of more abstract mathematical concepts (Bhatia & Sury, 2021). Furthermore, this study explains how zero and the decimal numeral system spread to the Islamic world through networks of trade, scientific text translation, and the growth of intellectual centers such as Baghdad. Muslim scholars, including Al-Khwarizmi, expanded the use of zero and made it an essential foundation for the development of algebra and practical arithmetic (Gonzalez, 2022; Mawardi, 2020). From the Islamic world, this numeral system later entered Europe through Andalusia and Mediterranean trade relations, eventually being reintroduced and popularized by figures such as Fibonacci, becoming a key component of the modern mathematical system (Kumar, 2023; Hassan & Karim, 2019).This study asserts that the conceptual journey of zero is the result of cross-civilizational knowledge exchange that shaped the foundations of modern mathematics and science